Screening Gogo Rice Local Aceh Cultivars Drought Tolerant Under Polyetilene Glycol 6000 - Muhammad Syahril; Syamsul Bahri; Rhido Suhada (Talenta Publisher, 2019)
Efforts for increasing rice production nationally, it is necessary to increase the productivity of a land. Utilization of marginal lands like drought land potential to increase rice production nationally. One effort to utilize marginal land like dry land is the use of high-yielding drought tolerant varieties. Until now high-yielding drought tolerant varieties still relatively rare. For this reason, it is necessary to create high-yielding drought tolerant varieties from plant breeding program. One of the standard programs in plant breeding to create high-yielding drought tolerant varieties is provision of genetic material as parental. Local varieties gogo rice Drought-tolerant potential to be used as parental in the plant breeding program to create of high-yielding drought tolerant rice varieties. For this reason, it is necessary to test drought tolerance of local rice cultivars. The study used 10 cultivars exploration results in East Aceh Regency namely Gameso, Sibengkok, Ramos Gunung, Sidol, Sigedul, Rias Kuning, Rias putih, Sibontok, Serumu, and Sileso. Drought tolerance testing using PEG solution (Polyethylene Glycol) 6000 156. 75 g / liter of H2O which is equivalent to the osmotic potential of -3 BAR and aquades as control (0 BAR) an germination stage and early vegetative stage. The results of the study show that 10 cultivars tested in the germination stage, 6 cultivars were selected as drought tolerant cultivars. Furthermore, 6 cultivars tested in the early vegetative stage showed the ability to recover at day 35 and then at day 42 showed no symptoms of drought. 6 drought tolerant cultivars are Gameso, Ramos Gunung, Sigedul, Rias Kuning, Sibontok, and Sileso.